Séries temporais combinadas com monitoramento estatístico para uso como ferramentas de gestão dos indicadores mensais de produtividade e resolutividade do Ministério Público do Estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
With the approval of the Brasília Charter in September 2016, the Brazilian Public Ministry assumed the commitment to be excellent in productivity and resolution, both in acting before the Judiciary, and acting extrajudicially as an intermediary of social pacifi cation. In this work, we only evaluated the productivity of the Public Prosecutors’ Offices in the Capital. We applied statistical methods to the MPAM’s Functional Activities Report - RAF database, from January 2012 to December 2019. We compared the performances of Box-Jenkins Methodology models applied to the original data series, then we chose the best model, which generated a sequence of appropriate data that were used in the statistical monitoring of the Control Chart CUSUM. The results obtained prove that the implementation of these methodologies, as long as they are in the online environment, will provide secure support to productivity management, resolution and decision-making within the scope of the MPAM.
Time series combined with statistical monitoring for use as management tools for monthly MPAM productivity and resoluteness indicators
Keywords: CIENCIAS EXATAS E DA TERRA; Metodologia de Box-Jenkins; Método SARIMA; Carta de Controle CUSUM.